WASMII: a data driven computer on a virtual hardware - Ling, X.-P.; Amano, H. (IEEE Workshop on FPGAs for Custom Computing Machines : proceedings, April 5-7, 1993, Napa, California, 1993)
Virtual hardware is a technique to realize a large digital circuit with a small real hardware by using an extended Field Programmable Gate Array (FPGA) technology. Several configuration RAM modules are provided inside the FPGA chip, and the configuration of the gate array can be rapidly changed by replacing the active module. Data for configuration are transferred from an off-chip backup RAM to an unused configuration RAM module. A novel computation mechanism called the WASMII, which executes a target data flow graph directly, is proposed on the basis of the virtual hardware. A WASMII chip consists of the FPGA for virtual hardware and the additional mechanism to replace configuration RAM modules in the data driven manner. Configuration data are preloaded by the order which is assigned in advance with a static scheduling preprocessor. By connecting a number of WASMII chips, a highly parallel system can be easily constructed.< >